2011
DOI: 10.1016/j.ajhg.2011.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Recessive Mutations in POLR3B, Encoding the Second Largest Subunit of Pol III, Cause a Rare Hypomyelinating Leukodystrophy

Abstract: Mutations in POLR3A encoding the largest subunit of RNA polymerase III (Pol III) were found to be responsible for the majority of cases presenting with three clinically overlapping hypomyelinating leukodystrophy phenotypes. We uncovered in three cases without POLR3A mutation recessive mutations in POLR3B, which codes for the second largest subunit of Pol III. Mutations in genes coding for Pol III subunits are a major cause of childhood-onset hypomyelinating leukodystrophies with prominent cerebellar dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
130
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 144 publications
(147 citation statements)
references
References 21 publications
6
130
0
8
Order By: Relevance
“…Lysates from all patients examined were strongly impaired in their ability to convert AT-rich DNA to immune-stimulatory RNA, whereas transcription of 5S rRNA was largely unaffected. Previous studies have identified mutations in POLR3A and POLR3B in patients with autosomal recessive 4H (hypomyelination, hypodontia, hypogonadotropic hypogonadism) leukodystrophy, which is a disease characterized by degeneration of the white matter in the brain (38)(39)(40). However, the functional impact of the POLR3 gene mutations in the 4H leukodystrophy patients on POL III activity remains to be established.…”
Section: Induction Of Ifns By At-rich Dna In Human Pbmcs Is Pol Iii-dmentioning
confidence: 99%
“…Lysates from all patients examined were strongly impaired in their ability to convert AT-rich DNA to immune-stimulatory RNA, whereas transcription of 5S rRNA was largely unaffected. Previous studies have identified mutations in POLR3A and POLR3B in patients with autosomal recessive 4H (hypomyelination, hypodontia, hypogonadotropic hypogonadism) leukodystrophy, which is a disease characterized by degeneration of the white matter in the brain (38)(39)(40). However, the functional impact of the POLR3 gene mutations in the 4H leukodystrophy patients on POL III activity remains to be established.…”
Section: Induction Of Ifns By At-rich Dna In Human Pbmcs Is Pol Iii-dmentioning
confidence: 99%
“…5 Mutations in POLR3A and POLR3B, encoding another subunit of this polymerase, were then shown to also cause 4H, as well as 2 other entities: "hypomyelination with cerebellar atrophy and hypoplasia of the corpus callosum," and "leukodystrophy with oligodontia." [6][7][8] The name Pol IIIrelated leukodystrophies has been suggested in order to include all the variations described above. As the term 4H encompasses the nonneurologic symptoms and is therefore clinically helpful for the diagnosis, we chose to refer to the condition as 4H leukodystrophy in this article.…”
mentioning
confidence: 99%
“…1,2 Mutations in the POLR3A and POLR3B genes, which encode for the 2 largest subunits of the RNA polymerase III (POLR3) complex, as well as in POLR1C, also encoding a POLR3 subunit, are responsible for this disease. [6][7][8][9][10][11] With the identification of the causative genes, patients with suggestive clinical or MRI picture can undergo genetic testing, confirming the diagnosis. 12 The MRI pattern of POLR3-related leukodystrophy is suggestive and characterized by diffuse hypomyelination associated with relative T2 hypointensity of the ventrolateral thalamus, globus pallidus, optic radiation, corticospinal tract at the level of the internal capsule and dentate nucleus, cerebellar atrophy, and thinning of the corpus callosum.…”
mentioning
confidence: 99%